Providing Health Information to Latino Farmworkers: The Case of the Affordable Care Act. Issue 3 (3rd July 2017) - Arcury, Thomas A.; Jensen, Anna; Mann, Mackenzie; Sandberg, Joanne C.; Wiggins, Melinda F.; Talton, Jennifer W.; Hall, Mark A.; Quandt, Sara A.
ABSTRACT: Objective: Providing health program information to vulnerable communities, such as Latino farmworkers, is difficult. This analysis describes the manner in which farmworkers receive information about the Affordable Care Act, comparing farmworkers with other Latinos. Methods: Interviews were conducted with 100 Latino farmworkers and 100 urban Latino North Carolina residents in 2015. Results: Most farmworkers had received health information from a community organization. Trusted sources for health information were health care providers and community organizations. Sources that would influence decisions to enroll were Latino nurses and doctors, religious leaders, and family members. Traditional media, including oral presentation and printed material at the doctor's office, were preferred by the majority of farmworkers and non-farmworkers. Farmworkers used traditional electronic media: radio, television, and telephone. More non-farmworkers used current electronic media: e-mail and Internet. Conclusions: Latino farmworkers and non-farmworkers prefer traditional media in the context of a health care setting. They are willing to try contemporary electronic media for this information.